Design And Simulation Of Resonant Tunneling Diode (RTD) Based High Frequency Monolithic Microwave Integrated Circuit (MMIC) - Chia, Ying Ying (Universiti Sains Malaysia, 2018)
Resonant tunneling diodes (RTD) are considered as the fastest semiconductor-based electronic devices demonstrated to date. They are promising for realizing a terahertz (THz) sources operating at room temperature by virtue of its unique characteristic of negative differential resistance (NDR). However, the main limitation of RTD based oscillators up to now is their low output power due to parasitic bias oscillations and small device dimensions. Hence, this paper has demonstrated a series of monolithic microwave integrated circuit (MMIC) oscillators with the appropriate RTD models created. The final aim of this work was to create an optimized RTD model to be implemented into MMIC RTD oscillators. The RTD model was created using different material systems based on current-voltage (I-V) characteristic with some important DC parameters such as peak current density, Ip, peak voltage, Vp and peak-to-valley-current ratio (PVCR). The RTD device consists of a narrow bandgap layer (quantum well) sandwiched between two thin wide bandgap layers (barriers). When the RTD is biased, electrons with kinetic energy lower than the barriers may tunnel through the double barrier quantum well (DBQW) structure, and the device will exhibit a negative differential resistance (NDR) in I-V curve. This property is very essential in the circuit application because it can provide for the different voltage-controlled logic states corresponding to the peak and valley currents. So, a well-suited range of I-V curve was modelled for RTD device so that it can be fitted in oscillator circuit accurately. In this project, one of the challenges was to solve the limitations of low output power of RTD oscillators. Thus, in this work, a series of monolithic microwave integrated circuit (MMIC) RTD oscillators has been presented. One of the oscillator circuit topologies is by applying two RTD devices in parallel. While each device is biased separately. Compared with single RTD oscillators, double RTDs oscillator can maximize the output power. This work proves the promising potential of RTD device in MMIC oscillators as Terahertz (THz) sources for a variety of applications especially high-speed wireless communication.